Autobiographical Memory for Emotional Events in Amnesia - Irene Daum; Herta Flor; Susann Brodbeck; Niels Birbaumer (Behavioural Neurology)
This study investigated autobiographical memory for emotionally flavoured experiences in amnesia. Ten amnesic patients and 10 matched control subjects completed the Autobiographical Memory Interview and three semi-structured interviews which assessed memory for personal events associated with pain, happiness and fear. Despite retrograde amnesia for autobiographical facts and incidents, amnesics remembered a similar number of emotionally significant personal experiences as control subjects. Their recollections generally lacked elaboration and detail, but pain-related memories appeared to be more mildly impaired than memories associated with happiness and fear. The findings are discussed in relation to recent views on the relationship between affect and memory.